The Kohistan Sequences: Crust and Mantle of an Obducted Island Arc - Bard, J.P; Maluski, H.; Matte, Ph.; Proust, F. (Journal of Himalayan Earth Sciences, 1980)
The Kohistan sequence outcrops in the western part of the western Himalayan syntaxis. It is a thick pile (3040 km) of metamorphosed magmatic, volcanic and sedimentary rocks. It is composed of six main units i.e. from bottom to top: - the southern amphibolitlc belt with basal ultramafics, - the "pyroxene granulite" belt (10-15 km thick), - the northern amphibolitic belt, intruded by various dioritic bodies, - a metasedimentary oceanic series (Kalam series), - a volcanic calc-alkaline series (Utror Volcanics), up to 6-8 km thick, - an upper detrital series (Yasin group, Lower Cretaceous). This sequence is interpreted as a complete cross-section of a mature island arc formed by subduction during Mesozoic in the southern part of the Neotethys and obducted onto the Indian plate in Upper Cretaceous times.